计算(2x+3y)(3x-2y)-(3x+2y)(3x-2y)
2个回答
(2x+3y)(3x-2y)-(3x+2y)(3x-2y)
=(3x-2y)(3x+2y+2x+3y)
=(3x-2y)(5x+5y)
=15x²+5xy-10y²
相关问题
计算(-x-2y)∧2-(x-y+3)(x+y-3)-(2y-x)(x+3y),
计算 :(2x-y)(2x+y)-(3x-2y)(-3x-2y)
计算:(2x-3y)2-(2x+3y)(2x-3y)=______.
计算:[(x+y/x-y)^2·(2y-2x/3x+3y)]-[(x^2/x^2-y^2)/(x/y)]
计算:(2x-3y)^2-(y+3x)(3x-y)
(1) (3x-2y)(y-3x)-(2x-y)(3x+y) (2) (3x+2y+4)(5x-2y-1) 计算
计算:(1)(-7x2-8y2)•(-x2+3y2)=______;(2)(3x-2y)(y-3x)-(2x-y)(3x
计算(2x^3-3x^2y-2xy^2)-(x^3-2xy^2+y^3)+(-x^3+3x^2y-y^3)
[x(x^2y^2-xy)-y(x^2-x^3y)]3x^2y计算,
计算 (1)[(x+2)(x-2)]^2 (2)(x+2y-3)(x-2y+3)(3)(x+y)^2(x-y)^2-(x